Essential emergency and critical care as a health system response to critical illness and the COVID19 pandemic: what does it cost? - Guinness, L; Kairu, A; Kuwawenaruwa, A; Khalid, K; Awadh, K; Were, V; Barasa, E; Shah, H; Baker, P; Schell, CO; Baker, T (BioMed Central, 2023)
Essential Emergency and Critical Care (EECC) is a novel approach to the care of critically ill patients, focusing on first-tier, effective, low-cost, life-saving care and designed to be feasible even in low-resourced and low-staffed settings. This is distinct from advanced critical care, usually conducted in ICUs with specialised staff, facilities and technologies. This paper estimates the incremental cost of EECC and advanced critical care for the planning of care for critically ill patients in Tanzania and Kenya.